Risk factors of unintentional injury among children in New Zealand: a systematic review - Luam Ghebreab; Bridget Kool; Arier Lee; Susan Morton (Elsevier, 2021)
Abstract Objective: To identify contemporary studies investigating multifaceted and inter‐linked contributory frameworks for unintentional injuries among children in New Zealand. Methods: A literature review was performed in seven databases. Studies published in English up to February 2020 reporting risk factors for child injury in New Zealand were included. Eligible study designs included: cohort, case‐control and case‐crossover studies. The quality of studies was assessed using the GATE frame tool. The PRISMA (Preferred Reporting Items for Systematic Reviews and MetaAnalyses) reporting guidelines were followed. Results: Thirteen studies fulfilled the inclusion criteria, dating from 1977 to 2008. The factors associated with child injury (0 to 14 years) included socioeconomic disadvantage, number of children, younger maternal age and sole parents. Vehicle speed and traffic volume were associated with an increased risk of driveway‐related pedestrian injury. Conclusion: The review findings have reinforced the need for cross‐agency action to address the social determinants of child injury. Implications for public health: Contemporary longitudinal studies are needed to assist in understanding how the interactions between children, family and their wider societal context affect their risk of experiencing injury over time.